Comparison Analysis of Rula Scores on Improvement Workplace Design in Concrete Brick Manufacturing SMEs - Nugraha, MH; IR, Anes; Widyantoro, Widyantoro; Rohman, Abd; Kostaman, Tata (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Paving block is constructions material usually used for form wall on building or construction jobs. Quality C dan D paving block manufacture on SMEs Scale in Tasilkmalaya Village does not have proper workplace design so that molder operator work in squat position. Squat position in manufacture paving block process is increasing RULA Score and ergonomic risk for musculoskeletal disorder (MSDs). In previous research, improvement has been applied to workplace, it has successfully increased productivity, but it is not sure can decrease ergonomic risk musculoskeletal disorder (MSDs) and RULA Score. This research aim to identify and compare the RULA Score before and after improvement. Analysis methods is used Rapid Upper Limb Assessment (RULA) with CATIA on moves element which has break down with Theblig methods. The result of research is workplace improvement has successfully decreased levels of ergonomic risk 43%.